Cycloserine Induced Psychosis, Insomnia and Suicidal Attempts in a Young Female Patient with Pre-Extensively Drug Resistant Tuberculosis - Priyanka Pravinbhai Hotha; Shubhima Grover; Rachna Gupta (Research Center for Rational Use of Drugs (RCRUD), 2022)
The World Health Organization classifies cycloserine as a group four second line anti tubercular drug for the treatment of drug resistant tuberculosis. Neuropsychiatric adverse drug reactions associated with cycloserine need more attention as they may compromise treatment success. Here, we report a case of cycloserine induced psychosis, insomnia and suicidal attempts in a young female patient with pre-extensively drug resistant tuberculosis (pre-XDR-TB). A 20-year-old female patient was prescribed longer oral XDR-TB regimen (high dose of moxifloxacin, cycloserine, linezolid, clofazimine, bedaquiline and pyridoxine). After fifteen days of treatment, patient developed changes in behaviour with frequent episodes of spontaneous and excessive laughing or crying. She also developed insomnia, started to hear voices and made two attempts of suicide. Following this, cycloserine was discontinued. Clonazepam and clomipramine were prescribed to her. Patient gradually recovered over a period of one month. Extreme caution with regular and close monitoring should be exercised while administering cycloserine because psychiatric adverse drug reactions could be associated with increased risk of poor drug adherence in drug resistant tuberculosis.